Red queen - Aveyard, Victoria (2015)
In a world divided by blood--those with common, Red blood serve the Silver-blooded elite, who are gifted with superhuman abilities--seventeen-year-old Mare, a Red, discovers she has an ability of her own. To cover up this impossibility, the king forces her to play the role of a lost Silver princess and betroths her to one of his own sons. But Mare risks everything and uses her new position to help the Scarlet Guard --a growing Red rebellion--even as her heart tugs her in an impossible direction.
Keywords: Teenage girls -- Fiction; Ability -- Fiction; Blood -- Fiction; Princesses -- Fiction; Government, Resistance to -- Fiction; Fantasy fiction; Young adult fiction